Navigating post-ICU care: understanding family members’ experiences - a qualitative study - Matteo Danielis; Alessandro Garau; Dina Molaro; Sara Gentilini; Marika Rosset; Serena Giorgino; Federica Vuerich; Renzo Zanotti; Lorenza Entilli (Health Psychology and Behavioral Medicine)
Background: Comprehending and addressing the needs of caregivers during the post-intensive care unit (ICU) phase is vital for establishing sustainable support systems and improving the overall quality of life (QoL) for both patients and caregivers.Objective: To explore the experiences of family members (FMs) caring for loved ones three-months after ICU discharge and their related QoL.Methods and measures: A qualitative, descriptive research was conducted. Participants were recruited from two general ICUs in an Italian Academic Hospital. Data collection lasted two months and was performed with telephonic interviews led by ICU nurses. Thematic analysis was conducted using a hybrid approach, incorporating both deductive and inductive coding strategies. This process has been facilitated by Atlas.ti software.Results: Twenty-four FMs participated, representing a diverse range of familial relationships with the patients. Thematic analysis revealed four overarching themes: 1) QoL underwent transformations; 2) Positive emotions laden with significance; 3) Supporting role taken on by a caregiver; and 4) Life’s transience through the meaning-making of the illness event. These themes highlighted the multifaceted nature of the caregiving experience.Conclusions: This study provides valuable insights into the challenges and dynamics faced by FMs following ICU discharge. Findings underscore the importance of addressing environmental challenges, cultivating positive emotions, and strengthening caregiver-patient relationships to enhance the caregiving experience and promote overall QoL. FMs can adapt their personal concepts and reach their full potential by learning to coexist with the demanding role of caregiver and achieve a new level of resilience and fulfillment.